واقع استخدام الاستراتيجيات التسويقية ودورها في زيادة الحصة السوقية "دراسة ميدانية في شركة الكمال لتنمية الصناعات الزراعية باللاذقية" - قاسم, سامر; بوّاط, غادة; غانم, سومر خليل (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يهدف هذا البحث إلى التعرف على واقع استخدام الاستراتيجيات التسويقية المتبعة في شركة الكمال للصناعات الزراعية, ومدى مساهمتها في تحسين مستوى أدائها العام وزيادة حصتها في السوق, ولتحقيق أهداف البحث تمّ بناء استبانة, وتطبيقها على عينة من العاملين في الشركة, وانتهى البحث إلى النتائج التالية: 1- تميل شركة الكمال للصناعات الزراعية إلى استخدام استراتيجيات التميز والترويج والتوزيع أكثر من ميلها لاستخدام استراتيجية التركيز والتنويع. 2- وجود علاقة ذات دلالة إحصائية بين الاستراتيجيات التسويقية (التميز والترويج والتوزيع) المطبقة في شركة الكمال وتحسين مستوى أدائها وزيادة حصتها في السوق. 3- عدم وجود علاقة ذات دلالة إحصائية بين الاستراتيجيات التسويقية (التركيز والتنويع) المطبقة في شركة الكمال وتحسين مستوى أدائها وزيادة حصتها في السوق. This research aims to get an idea about the situation of using the marketing strategies in Al-Kamal Co. for Agricultural Industries and its contribution in developing the level of its performance and increasing its market share. To achieve the research objectives, questionnaire was devised and applied on a sample of the workers in the company. The research concluded the following results: 1- Al-Kamal Co. for Agricultural Industries tends to use strategies of uniqueness and promotion more than its aim to use strategy of concentration and distribution. 2- There are statistically significant differences between the marketing strategies (uniqueness, promotion and distribution) that are applied in the company and developing the level of its performance and increase its market share. 3- There are no statistically significant differences between the marketing strategies (concentration and distribution) that are applied in the company and developing the level of its performance and increase its market share.